KONSUMTIVISME MASYARAKAT SATU DIMENSI DALAM OPTIK HERBERT MARCUSE - Andri Fransiskus Gultom (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2020)
AbstractConsumtivism has become the new ideology. It gives the meaning of life through material consumption as the way. In fact, this ideology made out social rationality and affected for method of thinking or social action must be measured by material calculation.This paper discusses to dismantle the meaning of consumptivism in society, which Herbert Marcuse called as one dimensional men. It was analyzed by Herbert Marcuse's critical theory of one dimensional men as far as to correct the impact of false needs and voluntary slavery in the consumptivism behavior of society. The goal is to restore the critical thinking of society in observing consumptive actions, who try to fullfil their priority of necessity. Cause, in fact, consumtive behaviour is a desire deliberately created by some interest group, that is the big investors, in order to get maximum profit.